PENERAPAN MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER BERBANTUAN MEDIA KARTU DOMINO UNTUK MENINGKATKAN CIVIC KNOWLEDGE PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI KELAS VIII B : Penelitian Tindakan Kelas Pada Mata Pelajaran Pendidikan Kewarganegaraan Kelas VIII B SMP Plus Babussalam Ciburial - Suci Mulyati (Civic Edu : Jurnal Pendidikan Kewarganegaraan, 2024)
ABSTRACK This study aims to improve students' civic knowledge through the implementation of the Numbered Heads Together (NHT) learning model assisted by domino cards. This research employs a Classroom Action Research (CAR) method with a mixed-methods approach, combining qualitative and quantitative approaches. The study was conducted at SMP Plus Babussalam Ciburial in the subject of Pancasila Education. The subjects of this study were 27 students from class VIII B. Data collection was carried out through observation, tests, interviews, and questionnaires. Qualitative data were analyzed using descriptive techniques, while quantitative data were analyzed using descriptive statistics. The results of the study indicate that the implementation of the NHT learning model assisted by domino cards significantly improves students' civic knowledge. This is evident from the increase in the average civic knowledge score of students from 56% in the first cycle to 64%, then to 71% in the second cycle, and reaching an average of 80% in the third cycle. Additionally, there was an increase in students' activeness and participation during the learning process. The obstacles faced in implementing this model included students' difficulties in understanding the initial instructions, limited time for conducting the domino card game, and the teachers' lack of skills in managing the class with the domino card media. These issues can be addressed through appropriate time adjustments and teacher training. Based on the results of this study, it can be concluded that the NHT learning model assisted by domino cards is effective in enhancing students' civic knowledge in Pancasila Education. It is recommended that teachers implement this learning model as an alternative to improve the quality of learning and students' understanding of civic education material. Keywords: Numbered Heads Together, Domino Cards, Civic Knowledge, Pancasila Education, Classroom Action Research.